Structures and geometries of the Tajo Basin crust, Spain: Results of a magnetotelluric investigation compared to seismic and thermal models. Issue 9 (18th September 2014) - Schmoldt, J.‐P.; Jones, A. G.; Rosell, O.
Abstract The Tajo Basin and Betic Mountain Chain in the south central region of the Iberian Peninsula were chosen for investigation in the first phase of the magnetotelluric (MT) component of the PICASSO (Program to Investigate the Convective Alboran Sea System Overturn) project. The MT results provide information about the electrical conductivity distribution in previously unprobed subsurface regions, as well as complimenting and enhancing results of prior geological and geophysical investigations thereby enabling the definition of a petrological subsurface model and a comprehensive understanding about the tectonic setting. Two‐dimensional (2‐D) inversion of the MT data provides enhanced insight into Iberian subsurface geology in the crust. The most striking features of the final model are (i) a distinct vertical interface within the Variscan basement beneath the center of the Tajo Basin that is spatially associated with the boundary between regions with and without substantial Alpine deformation, and (ii) a middle to lower crustal conductive anomaly that can be related to remnants of asthenospheric intrusion in connection with Pliocene volcanic events in the Calatrava Volcanic Province. For the latter, effects of hydrous phases are inferred that may originate from dehydration processes within the subducting slab beneath Alboran Domain and Betic Mountain Chain.